POLA PEMANFAATAN LAHAN BERBASIS PENGETAHUAN LOKAL DI WILAYAH KPHP MODEL SIVIA PATUJU KECAMATAN AMPANA TETE KABUPATEN TOJO UNA-UNA - Harmia, Harmia; Golar, Golar; Rahmawati, Rahmawati (Jurnal Warta Rimba, 2017)
The use of land especially at upload area tend to cause environment degradation. It can cause a serious threat for now and the future. When farmers development technology failed at dry land and high land, it can be seen as the fail of an effort repair especially at upload. It means that the threat is getting close to villagers. Meanwhile, natural resources is limited. When the use of land do not follow by theÂ  attention to the function of the land, it can caused the damage and threat the preservation of natural resources and it influenced by geobiofisik land, social and culture, and economics. The objective of the research is too know the use of local knowledge at KPHP Model Sivia Patuju, District of Ampana Tete, Tojo Una una Regency. The research was conducted from October to December 2014 at Pusungi Village, District Ampana tete, Tojo Una una Regency. This research is analyzed descriptively and based on forest resources, namely : (1) sought plant, (2) conservation, (3) cropping, (4) land mastering. The result of the research show that the people use agroforestry system, namely agrisilvikultur with combining plant. The form is based on land choosing, land burning, cleaning land, the way in choosing the plant, the form of planting, and time in planting. The villagers knowledge commonly adapted to social aspect and people culture.Key Words: The use of land, Local knowledge, KPH.